2011
DOI: 10.1002/ase.197
|View full text |Cite
|
Sign up to set email alerts
|

A case study on multiple‐choice testing in anatomical sciences

Abstract: Objective testing techniques, such as multiple-choice examinations, are a widely accepted method of assessment in gross anatomy. In order to deter cheating on these types of examinations, instructors often design several versions of an examination to distribute. These versions usually involve the rearrangement of questions and their corresponding answer choices. This study will determine whether the distribution of different versions of an examination affects student performance in a lower division anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Like most areas of academia, examinations most often are comprised of multiple choice questions (MCQ). While not the only way to assess anatomical knowledge, MCQ examinations are relatively easy to administer and results can be obtained quicker than most other assessment methods (Jozefowicz et al, ; Severo and Tavares, ; Golda, ). While there are many critiques of MCQ examinations (Godfrey, ; Jozefowicz et al, ; Crisp and Sweiry, ; Clifton and Schriner, ), their popularity has not appeared to diminish.…”
Section: Introductionmentioning
confidence: 99%
“…Like most areas of academia, examinations most often are comprised of multiple choice questions (MCQ). While not the only way to assess anatomical knowledge, MCQ examinations are relatively easy to administer and results can be obtained quicker than most other assessment methods (Jozefowicz et al, ; Severo and Tavares, ; Golda, ). While there are many critiques of MCQ examinations (Godfrey, ; Jozefowicz et al, ; Crisp and Sweiry, ; Clifton and Schriner, ), their popularity has not appeared to diminish.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about students' perceptions and motivations that lead them to prefer RL or SDL approaches, as well as their preferences for CLS, is necessary to better understand students' learning processes in medical histology (Hilliard, 1995). Different studies have identified several factors that may influence the educational process significantly, including gender, attitude, and the instructional methods used (Barnes et al, 2005; Golda, 2011). A further consideration is that in medical education, gender issues have become more important for academicians, health administrators, and society in general, mainly because of the increasing feminization of the medical profession.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are challenges associated with MCQ assessments, it is commonly accepted that MCQs can be used to test a variety of Bloom's taxonomy performance levels (Aiken, ; Morrison and Free, ; Brady, ; Palmer and Devitt, ; Clifton and Schriner, ; Tiemeier et al, ). A wealth of information is available to aid with the writing of efficient and fair MCQs (Case and Swanson, ; Haladyna et al, ; McCoubrie, ), especially for use in medical examinations (Downing, ; Golda, ). Ideally, MCQs are written to assess higher‐order thinking skills.…”
Section: Introductionmentioning
confidence: 99%